PREVALENCE OF HIRSUTISM IN ADULT FEMALES IN GYNAECOLOGY OUT PATIENT CLINIC AT TIKRIT TEACHING HOSPITAL - Ghalib, Ayla Kh.; Talir, Suheila Sh. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Hirsutism is a common clinical problem which causes a great distress to the patient, which true incidence is unknown . However it is more common among Mediterranian women who are usually more accepting of their condition . Aim of study : To determine the prevalence of hirsutism among adult females attendins the gynaecology out patient clinic at tikrit teaching hospital. Patients & Methods: A sample of 175 adult non pregnant women (married & un married) with age range (18-25) years was included in this study .All attending the Gynaecology out patient clinic in Tiktrit teaching Hospital from Jan-Oct. 1999 .A full medical history was obtained. then patient were examined for pattern and severity of hair gowth . Grading was done usin , ferryman and Gallway scoring system . Results : the prevalence of hirsutism was (35.4%) , when sevesity of hirsutism was assessed majority of patients (77.5%) had grade I hirsutism . yirilizing symptoms and signs were found in (69.3%) . the family history for the same condition in the family was positive in (24.1%) of hirsute women (67.8%) of hirsute women showed one or more of sonographic features ofpolycystic ovarian syndrome. The Body was found to differ in hirsute women compared to normal